2021
DOI: 10.1038/s41586-021-03901-9
|View full text |Cite
|
Sign up to set email alerts
|

Resurgence of Ebola virus in 2021 in Guinea suggests a new paradigm for outbreaks

Abstract: Seven years after the declaration of the first epidemic of Ebola virus disease in Guinea, the country faced a new outbreak-between 14 February and 19 June 2021-near the epicentre of the previous epidemic 1,2 . Here we use next-generation sequencing to generate complete or near-complete genomes of Zaire ebolavirus from samples obtained from 12 different patients. These genomes form a well-supported phylogenetic cluster with genomes from the previous outbreak, which indicates that the new outbreak was not the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
88
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 52 publications
1
88
0
4
Order By: Relevance
“…Persistent SARS-CoV-2 infection is observed in immunosuppressed individuals 76 78 and is rather unlikely to be the reason for the observed sudden rise in virus-neutralizing antibodies in healthy convalescents. However, the establishment of latent infection has recently been proposed for RNA viruses such as Ebola virus 79 , and may potentially also apply for SARS-CoV-2 that can infect immune-privileged sites such as the central nervous system 80 . Furthermore, it is possible that an increase in antibody affinity after SARS-CoV-infection 54 may have contributed to the observed increase in virus-neutralization activity in convalescents.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent SARS-CoV-2 infection is observed in immunosuppressed individuals 76 78 and is rather unlikely to be the reason for the observed sudden rise in virus-neutralizing antibodies in healthy convalescents. However, the establishment of latent infection has recently been proposed for RNA viruses such as Ebola virus 79 , and may potentially also apply for SARS-CoV-2 that can infect immune-privileged sites such as the central nervous system 80 . Furthermore, it is possible that an increase in antibody affinity after SARS-CoV-infection 54 may have contributed to the observed increase in virus-neutralization activity in convalescents.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of EVD outbreaks occurred in remote areas and remained geographically restricted, but the recent outbreaks in West Africa (December 2013 to March 2016) and in Eastern DRC (August 2018 to June 2020) clearly showed that thousands of individuals can be infected over large geographic areas [ 3 ]. From these larger epidemics, it is evident that certain EVD outbreaks can be linked to individuals who recovered from the disease, even after more than five years [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of subsequent EVD outbreaks -approximately every other year since 1976-as October 1, 2021 1/24 well as their locations -overwhelmingly in the sub-Saharian region-reveals the dimension of a problem that is endemic to the African continent. New evidence hints at the possibility of latency as one of the mechanisms to explain this endemism [7]. As a matter of fact, at the time of preparation of this manuscript there were ongoing outbreaks in Guinea and in the Democratic Republic of Congo.…”
Section: Introductionmentioning
confidence: 88%